GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 272846321 species occurrences available in GBIF matching the query: TaxonKey: Aves. The dataset includes 272846321 records from 1742 constituent datasets: 72 records from Schatzinsel Wangerooge. 2 records from BB-Biodiversität b. 28 records from Schieferbrüche. 26 records from Oberes Schindelbachtal. 3 records from "Schlechteberg" Ebersbach/Sa.. 8 records from Wiesendreieck Luckenwalde. 1 records from Artenvielfalt auf Zollverein. 1 records from Fliegenhaupt Marksuhl. 43 records from Grünes Germersheim. 94041 records from ArtenFinder. 2 records from SysTax - Botanical Gardens. 121 records from BIRDRACE Die Schwenker-Birder. 7 records from Mönchspark. 52 records from Himmelmoor. 3768 records from Eggs Specimen. 9 records from Zitadelle Berlin-Spandau (7b). 9 records from Erft in Selikum (Neuss). 42 records from FFH-Gebiet "Calwer Heckengäu". 21247 records from Animal Sound Archive. 12 records from Bolzplatz. 3 records from Isartal Dingolfing. 2 records from Estetal (Buxtehude). 6883 records from Kingfisher Survey 2010. 258343 records from WFVZ Bird Collections. 8 records from Rund um den Hainbergsee. 3 records from MfN - Fossil vertebrates III. 65 records from Cuxhavener Küstenheiden. 72 records from Pilstingermoos. 54 records from Kohlstattbrunnental. 6 records from Collection Crustacea SMF. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 8 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 6 records from The Distribution Atlas of Butterflies in Poland. 87 records from Schatzinsel Norderney. 55 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 1727 records from Birds collection of Abiko City Museum of Birds. 91 records from BIRDRACE NABU LV Hessen. 11 records from Pflanzen und Tiere im Burgwald. 1 records from Naturpark Kottenforst-Ville 15.6.09. 45 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 15 records from Wismar Bucht coast-watching. 142 records from Birdrace-Alte_Socken-Cuxhaven. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 10 records from NIAES Coleoptera Specimen Database. 3200 records from ISU Birds. 86 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 111 records from Birdrace-Uhulogen-Lippe. 8 records from Rund ums Schulgelände. 27 records from Bugbase, Lepidopterological Society. 26001 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 480819 records from KTP Ring Data. 27079 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 46 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 6 records from GymnQuerfurt. 274 records from BIRDRACE Asiola-Quartett. 3350 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from verschiedene Kleingewässer um Oldenburg/Holstein. 54 records from NSG Leist bei Ziegenhain. 3 records from Regenwasserabfangsbecken (Erlenbach). 2 records from Mühlenbach bei Buxtehude. 102 records from BIRDRACE Willi goes Birding. 2 records from MfN - Fossil vertebrates IV. 1 records from Botanical Garden Collection. 10800 records from Database Schema for UC Davis Wildlife museum. 7400 records from University of Alberta Museums, Ornithology Collection. 21 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 1 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 1 records from Palaeobiology collection, FAU Erlangen. 42654 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 20 records from BTCV Scotland - BTCV wildlife counts recording workshops. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 34013 records from Lund Museum of Zoology (MZLU). 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 8 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 4 records from Naturhausgarten. 4 records from Mauernacker (Wettsaasen). 1 records from Amtsrain Apolda-Zottelstedt. 8 records from NABU-Auerochsenweide. 6 records from Regenwasserabfangbecken. 6 records from Schulgelände Lise Meitner Realschule (Paderborn). 7 records from Salzwiese Diekskiel. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 84 records from BIRDRACE Avinauten. 102 records from BIRDRACE Westfälische Nachtigallen. 2 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 25989 records from SysTax - Zoological Collections. 2 records from Herbarium BSG Bryophyta. 3 records from Angelberger Forst - Klassen 3 a und 3 b. 3 records from Teich Berlin Wuhlheide. 14522 records from MVZ Egg and Nest Collection (Arctos). 1636 records from Ájtte. 3329819 records from OEH Atlas of NSW Wildlife. 2846 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 29840 records from Birds collection of Yamashina Institute for Ornithology. 109 records from Birdrace-Team_Charadrius-Günzburg. 8 records from Waldhusener Moor (Lübeck-Kücknitz). 6 records from Flusswerder in der Weser (Hameln). 9 records from Steinbruch Mainz-Weisenau, 2. Jahr. 19 records from Diveboard - Scuba diving citizen science observations. 45 records from Inventario nacional de especies vegetales y animales de uso artesanal. 7926 records from NBM birds. 48112 records from MMNH Museum Bird Collection. 61 records from Mooswald (Freiburg). 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rheidae. 26799 records from Bird Monitoring Data. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 10 records from VFD HH/SH "Pferdeweide Lemsahl". 3 records from Nationaal Herbarium Nederland. 2072 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 40 records from Naturschutzstation Schmidsfelden. 1 records from University of Florida Invertebrate Paleontology. 28277 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1988-1992. 22 records from MfN - Fossil Fish Collection. 22334 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 6 records from Bonner Schülerinnen am Rodder Maar. 1 records from Collection Ichthyologie - SNSD. 12 records from Tiergarten Straubing. 1388 records from Caracterización de aves del borde sur de Bogotá en las localidades de Usme y Ciudad Bolívar. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 100 records from Birdrace-Meister_der_Herzen-Kleve. 13 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 166 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 89 records from Birdrace-Team_Wangerooge-Friesland. 139 records from BIRDRACE Turbine Untersee. 1 records from Hausgarten. 7 records from Streuobstwiese Stedar 2008. 110564 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 49 records from Schlichemquelle (Tieringen/Meßstetten). 4 records from Tiergarten (Zeitz). 80 records from Lustadter Wald .. 53 records from Tag der Artenvielfalt im Taubental. 205443 records from CM Birds Collection. 16 records from Paleontological collection of the National Museum - Fauna. 638158 records from Fauna Atlas N.T.. 105 records from Birdrace-ARKONAuten-Rügen. 2 records from Alter Kreidebruch Saßnitz/Rügen. 18 records from Dorfrand Mauderode. 2 records from Birkenloh. 4 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 1 records from Schulgarten der Hainbuchenschule (Hagenbach). 7 records from Streuobstwiese Stedar. 24193 records from Joint Nature Conservation Committee - Seabird 2000. 15 records from Luderbusch. 4 records from iziko South African Museum - Fish Collection (AfrOBIS). 107 records from 1st Austrian Birdrace (Wien). 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 8441 records from BioFokus. 8025 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 3588 records from Natural History Museum Rotterdam (NL) - Chordata collection. 5 records from Wasser-Lernort Nettemündung. 1368 records from Bird Collection of Yokosuka City Museum. 8334 records from Birds (GMBO-BI). 80 records from BÜG. 14 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 376 records from National Trust - Sutton Hoo species data held by The National Trust.. 22 records from Aphidoidea Collection. 164 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Arroyo Sauce Grande (Monte Hermoso). 2 records from NPL collections. 3942 records from TTRS Ornithology. 9 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 145 records from BIRDRACE Dith Marsh Sandpiper. 120 records from BIRDRACE The early birds. 4 records from Birkenpilz. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 16 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2 records from Ecofact. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 617129 records from Historical Bird Atlas. 145816 records from iNaturalist research-grade observations. 1 records from VFD-RP: Taunus: Ponykoppel Thurner. 4 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 4 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 32 records from Bodenteicher Seewiesen. 14 records from Binsenwiesen im Bizzenbachtal. 6 records from Schulgelände (Wetter). 47 records from Artenfülle um das Schalkenmehrener Maar. 29 records from NSG Nollig. 40 records from Vogelstimmenführung durch den Tiergarten. 4 records from An der Ohm, (Wettsaasen). 237 records from RSPB - Capercaillie national surveys (SCARABBS). 635 records from European Molecular Biology Laboratory Australian Mirror. 39790 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 10156 records from Vertebrats d'Andorra. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 26 records from Artenvielfalt rund um die Dalbek-Schule. 2014 records from Birds (NHMK-BI). 33 records from Naturschutzgebiet Sistig-Krekeler-Heide. 17 records from Blumenrather Heide / Virneburg. 1 records from Steinbruch Pluwig. 42414 records from Collection Aves (bird skins) SMF. 5484 records from IICT Colecção Zoológica. 81388 records from natagora-earlybirds. 328 records from Census of the animals of Benin. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 2 records from Spielwiese. 9 records from Tiere im Teichgebiet. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 1 records from Aachtobel. 1 records from Kirchenforst. 264 records from Mammal and Fish speciemens of Kumamoto City Museum. 61 records from BIRDRACE Bergische Ornis. 66 records from Biosphärenreservat Mittelelbe. 3005 records from Individual Sightings. 5 records from Umgebung von Schorndorf. 33 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 38 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Corvidae. 1947 records from RSPB - Lapwing Recovery Project, South West Scotland, 2006-2009, RSPB. 1 records from Scottish Natural Heritage - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by Scottish Natural Heritage. 39 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 26 records from Dalbekschlucht. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 4 records from Sternwiese Mülheim-Broich. 17 records from MfN - Fossil invertebrates Ia. 16 records from Plant (JNHM-PL). 108 records from BUND - Dassower See (Lübeck/Dassow). 6 records from Deutsche Schule Budapest. 44 records from Lebensraum Gesamtschule (Langerwehe). 20500 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1339 records from WNMU Bird Collection (Arctos). 132 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fringillidae. 1 records from Oregon State University Herpetological Collection. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 30 records from Zielbach (Töll). 35 records from Schussenaue bei Berg. 17 records from Stadtpark Schmölln. 48 records from Dornwanger Moos. 92 records from condoncollection. 37515 records from Bird Collection of Museum and Institute of Zoology PAS. 4852502 records from Bird Ringing Centre in Sweden (NRM). 112 records from Birdrace_Die_Borner-Viersen. 35 records from Varnhalt. 70 records from Bernhardsthal. 5 records from Schulgarten Zinnowwald-GS. 2 records from Feuchtbiotop Weidenkaule. 103455 records from ANTAVIA-TrackingKing. 668224 records from Ringing Data from the Bird Migration Research Station, University of Gdańsk. 15 records from Arizona State University Amphibian and Reptile Collection. 2 records from Knechtweide (Kohlfurth). 164153 records from Fieldjournal.org observation database. 9683973 records from Norwegian Species Observation Service. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 4 records from RSPB - Black grouse lek survey in Wester Ross and Skye 2009 (RSPB). 1 records from SysTax - Herbaria. 28 records from Deponie Klausdorf. 21 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 111 records from BIRDRACE Die Wendehälse. 1545 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 144660 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 58411 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 6623 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 103 records from Birdrace-Die_Nachtigallen-Herford. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 15 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 24 records from Schulgelände des Schulzentrums am Himmelsbarg. 25425 records from Birds (JNHM-BI). 49 records from RSPB - Turtle Dove sightings from research project in East Anglia, 2010. 155618 records from Natural History Museum (London) Collection Specimens. 31 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 35 records from Renaturierung Werse (Innenbereich Beckum). 2 records from Breitkopfbecken (Berlin-Reinickendorf). 5 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 101 records from BIRDRACE Enger am Spektiv. 90 records from BIRDRACE TicTacToe. 714 records from Tissues Specimens. 38 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 39978 records from Carpatica Operation. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cracidae. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 7070 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 91 records from Birdrace-Enger_am_Spektiv-Herford. 2 records from Trockenrasen Franzigmark (Halle/Saale). 5 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 3 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2. 274 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 51902 records from PIROP (Shipboard Surveys). 7 records from Schulhof Bühlschule Giengen. 113 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 20116 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 129 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 122 records from BIRDRACE Unterste Niederrhein-Rennvögel. 3 records from Königsdorfer Wald. 269 records from BIRDRACE speedbirder. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 1737 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 32801 records from UMZC Zoological Specimens. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 4 records from Röntgenarchiv Wilhelm Stürmer - SMF. 3007 records from Bird specimens in Gifu Prefectural Museum. 13628 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 30 records from Lahnufer in Villmar. 2 records from Lerchenauer Baggersee (München). 4 records from Landschaftsschutzgebiet Schmutterwald. 88 records from BIRDRACE Kingfisher. 35 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 13 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 7 records from Flora und Fauna im Brexbachtal. 3 records from Natural History Museum, Vienna - Herbarium W. 1 records from Collection Malakologie - SNSD. 6 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 82 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ciconiidae. 333 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Charadriidae. 81 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 408 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 149 records from Birdrace-Usedommeln-Ostvorpommern. 3 records from Rohrmeistereiplateau und angrenzendes Gebiet. 5 records from Unter hellen Zinnen und finsteren Grotten. 27 records from Porcupine Marine Natural History Society - Marine flora and fauna records from the North-east Atlantic. 2 records from Bumblebees, cuckoobees and butterflies in southern Poland. 9 records from Banc de dades de biodiversitat de Catalunya-MolusCat. 551 records from Carabidae of the Carpathians. 77 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 4 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 8 records from Klütwald. 2 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 7 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 3477 records from Aves laguna El Tinije. 65 records from Philosophenwald und Wieseckaue in Gießen. 87 records from Freigelände Naturschutzscheune Reinheimer Teich (Kreis Darmstadt-Dieburg). 9 records from Oberservation of birds at station PS14/142 along 49° West. 4783 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 8404 records from Upper Silesian Museum, Bird Observations. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 604 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 1636 records from Ibaraki Nature Museum, Birds collection. 348 records from Mammalia - Baekdu Mountain Animal (KIDR-MM). 41 records from Yorkshire Naturalists' Union Marine and Coastal Section - Yorkshire Naturalists Union Marine and Coastal Section Records. 2 records from Online Atlas of vascular plants 2012-2020. 16 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 6 records from Gewässeruntersuchung Grötzinger Baggersee. 2303 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 23146 records from BC Coastal Waterbird Survey. 21175 records from Birds Specimens. 3 records from Mammal tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 25 records from Database of invertebrates collected in Mongolia. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Podicipedidae. 410194 records from Inventario Español de Especies Terrestres (MAGRAMA). 30 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 4 records from Landschaftsschutzgebiet Buchhorst 4. 137 records from BIRDRACE Arkonauten. 27 records from Listhof und Umgebung. 2792 records from Birds (UWEP-BI). 323 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 1934 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tyrannidae. 10 records from invertebratezoology. 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 12 records from Artenvielfalt auf den Elbwiesen (Dessau). 69 records from Schulhof Goethe-Gymnasium (Emmendingen). 21 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 12 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 19 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mar del Plata (Pugnali, junio 1998). 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cariamidae. 8 records from Endocast Collection -CONICET- Argentina. 1385 records from Birds - Wild Birds (KIDR-BI). 1 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 14 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 2024 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 5927 records from Tasmanian Museum and Art Gallery provider for OZCAM. 39 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 7 records from Bachrenaturierung Littfe. 1343 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 23 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 1 records from Plant (NHMC-PL). 43 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 53 records from Unna-Mühlhausen, Wiesen. 425 records from ANTXXIII-8 Birds and Mammals (SCAR-MarBIN: Antarctic OBIS). 100 records from National Biodiversity Network Trust - Demonstration dataset for record commenting on the NBN Gateway. 13115 records from Instituto de ciencias naturales. 27156 records from Bird tissue collection, Natural History Museum, University of Oslo. 10839 records from Bird skin collection, Natural History Museum, University of Oslo. 11 records from Lassentiner Moor (Niepars). 3578 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009 â sensitive records. 27123 records from CNAV/Coleccion Nacional de Aves. 1 records from Danielsberg (Mölltal, Kärnten). 91 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 34 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña diciembre 2010. 1 records from dec2011. 1 records from CUMV Fish Collection (Arctos). 61 records from BIRDRACE Baumläufer. 6481 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 30 records from Halberg bei Neumorschen. 31 records from Seewasen. 35 records from renaturierter Main (Kemmern bei Bamberg). 29 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 11 records from Gymnicher Mühle. 1 records from Centre for Environmental Data and Recording - Marine Data from Northern Ireland. 3896 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 7370 records from Zoology (Museum of Evolution - Uppsala). 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 100 records from BIRDRACE Stuttgart 100 trööt. 1748 records from National Trust - Hatfield Forest species data held by The National Trust.. 3 records from Schulaktion des Dienzenhofer-Gymnasiums. 122 records from BIRDRACE Grenzgänger. 3 records from Herbarium BSG Vascular Plants. 28 records from Naturschutzgebiet Bausenberg. 18 records from Schulumfeld Albert-Einstein-Gymnasium (Sankt Augustin). 12 records from Alterra (NL) - Entomofauna inventory in peat swamps. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 108 records from Birdrace-TriumVIErat-Viersen. 27 records from Lech 2001. 21 records from Garten J. Scherrer (Lachen-Speyerdorf). 25 records from Landschaftspark St.Leonhard-Deisendorf. 7 records from Garten in Schmölln. 82 records from BIRDRACE Die Ziegeneier. 56 records from Bayerische Donau - Leipheim. 36532 records from Western Australian Museum provider for OZCAM. 30 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 5 records from Artenvielfalt auf dem Schulgelände. 55690 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 3 records from Observation of birds at station PS14/153 along 49° West. 33 records from Tag der Artenvielfalt mit SchülerInnen des Leibniz-Gymnasiums in Neustadt a.d.W.. 63985 records from The First Atlas of Breeding Birds in Britain and Ireland: 1968-1972.. 11964093 records from Tiira information service. 18 records from Römertal (Steinpleis). 1 records from Bachabschnitt der Nette (Osnabrück). 25 records from FFH-Gebiet Paartal. 21 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 7 records from Artenvielfalt in der Kinderakademie im RFZ. 66 records from Bulau. 18 records from 4. GEO-Tag in Eberbach. 6 records from Oberservation of birds at station PS14/148 along 49° West. 2 records from NINA Vanndata øvrige arter. 1 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 168 records from RSPB - Cetti's warbler national survey in the UK and the Channel Islands in 1996 (SCARRABS). 571 records from Northern Ireland Environment Agency - EHS Species Datasets. 45740 records from 2011 Breeding Bird Survey of Taiwan. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 299586 records from SEAPOP NINA. 26 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 32 records from Öhmdwiesen und Göldern (Konstanz). 6 records from Zwickau- Schwanenteich. 80 records from BIRDRACE Falkenberger Fluppis. 4 records from Liether Kalkgrube. 3964 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 4 records from Unser Schulgelände. 167 records from Birdrace-Nord_Seh_Team-Nordfriesland. 37 records from Freiburger Netzwerk Artenvielfalt. 701 records from Vertebrate Paleontology Division, Yale Peabody Museum. 3 records from MVZ Mammal Collection (Arctos). 28267 records from UAM Bird Collection (Arctos). 20 records from Rund ums Cani. 2 records from Schriesheimer Steinbruch. 3 records from Aktion - Friedensburg Oberschule. 301 records from Birds (GNHM-BI). 19386 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 1905 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 17139 records from Aves MZS. 58 records from Schlern - (Bozen). 2 records from Unser Schulhof. 7 records from Cresswell Associates - Wildlife Surveys in Southern Scotland 2007-2011. 388068 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 77 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 13942 records from NYSM Birds. 98 records from Birdrace-The_Ringers-Friesland. 19468 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 1 records from Animal observations. 59 records from Erlengraben/Lipp-Tal (Östringen). 49 records from Schwanheimer Wald. 3 records from NSG Dellwiger Wald, Dortmund. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 3 records from Goethe-Hauptschule/Projekt I-10. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 2 records from Issumer Fleuth. 1 records from Graureiher in Lans. 1 records from Haselbachtal. 181 records from Table I: Birds observed at the Weddell Sea during the period: 6 December 1955 to 19 January 1956. 139 records from Corvids Literature Database. 440437 records from Bird tracking - GPS tracking of Lesser Black-backed Gull and Herring Gull breeding at the Belgian coast. 5 records from Field Museum of Natural History (Zoology) Fish Collection. 209024 records from UMMZ Birds Collection. 2 records from Balkon (Norderstedt). 30 records from Zoo Frankfurt. 7 records from Tiere und Pflanzen um uns herum !. 258 records from BIRDRACE Raumpatrouille Oriolus. 131 records from BIRDRACE Griffin Wood Warblers. 84 records from BIRDRACE Birding for Nature. 88 records from BIRDRACE Vogelkucker. 53 records from BIRDRACE Taubenhaucher. 26 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thinocoridae. 131 records from STERNA dataset of the RMCA (Royal Museum for Central Africa) - Zoology/Ornithology Collection. 2073 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 41 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 62 records from Vorderer Tiergarten (Dessau). 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Procellariidae. 51707 records from EcoRecord - Bird records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 66 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 5 records from Marine species distributions in Irish coastal waters. 561034 records from Biologiezentrum Linz. 124 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 1162 records from Birds (KNAM-BI). 40 records from Föhrenried (Fronreute und Baindt). 2 records from Junge Heide, Radebeul/Dresden. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 7 records from Tiere und Pflanzen am Pfannenbach. 2 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 1 records from Collection Crustacea - SNSD. 49 records from UWFC Ichthyology Collection. 46 records from Stausee (Oberdigisheim/Meßstetten). 10 records from Schulgarten Huttenheim (Philippsburg/Baden). 2 records from Paleobotany Division, Yale Peabody Museum. 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory.. 5 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 36 records from Crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 3 records from Museu Paraense Emilio Goeldi - Ictiology Collection. 128 records from Birdrace-Brut-Wetteraukreis. 41 records from Entdeckertour am Muldestausee 1/05. 38 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 10 records from Naturschutzgebiet Swistbachaue (Eckendorf). 2 records from MfN - Fossil vertebrates V. 2705551 records from First Bird Atlas. 73544 records from Marsh Monitoring Program - Birds. 17 records from Hamberger Brücke / Würmtal (Pforzheim). 16182 records from Coleccion de sonidos ambientales. 67 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Guaminí (Carrique, octubre 1999). 12 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 3 records from Reusaer Wald. 143 records from BIRDRACE Punkbirder Helgoland. 35736 records from British Antarctic Survey Argos satellite tracking data. 12 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 134 records from Birdrace-Easy_Birders-Plön. 101 records from RSPB - Greenshanks national survey in the UK, 1995 (SCARABBS). 927 records from Inventaire National du Patrimoine Naturel : Inventaire du Parc national du Mercantour. 12 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester . 30 records from Regenrückhaltebecken (Zeulenroda). 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 1074 records from Ireland's BioBlitz 2012. 17543 records from Ornithology Collection. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 9 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 4870 records from Anymals+plants - Citizen Science Data. 59181 records from South Australian Museum Australia provider for OZCAM. 892 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 693 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 133 records from South Australia Flora Observations. 96 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 5 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 24 records from Feriendorf des Kreises Gedern (Ober-Seemen). 23 records from Naturerlebnisraum Koppelsberg (Plön). 9 records from Garten Hamburg Uhlenhorst. 174 records from BIRDRACE Bon(n)apartemöwen. 114 records from BIRDRACE VIE will rock you!. 107 records from BIRDRACE Borussia Zippammer. 10 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 7076556 records from Great Backyard Bird Count. 8 records from Invertebrate Zoology Division, Yale Peabody Museum. 38 records from Streuobstwiese Kugelberg (Ulm). 54 records from Naturerlebnisraum Koppelsberg. 2 records from Collection Aves fossil SMF. 108323 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 8 records from Ökologischer Weinberg (Guntersblum). 7139 records from Snow Petrel census, Reeve Hill, Windmill Island, East Antarctica (1984-2003). 1 records from Atlaszeder in Oma´s Garten. 52076 records from Birds (KIEE-BI). 4 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 26721 records from Bird Observational Records. 2571 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 4 records from AKG-Gelände (Bensheim). 42 records from katzenbuckel. 44 records from Wald am Schloss Wittgenstein Bad Laasphe. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 1 records from Collection Mollusca SMF. 139 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 54 records from Weidegebiete in der Selzrenaturierung. 210 records from RSPB - Black grouse lek survey in the Scottish Borders, 2010 (Southern Upland Partnership). 72 records from Merseyside BioBank - Merseyside BioBank NBN Frequently Updated Taxa. 4 records from MfN - Mallophaga Collection. 5638 records from Estacion Biologica Donana - CSIC, Aves. 1 records from Osaka Prefectural Minoh Park Insects Museum. 16 records from Hüttenseepark (Meißendorf). 32 records from Hintere Halde. 13607 records from Fundación Miguel Lillo - Colección Ornitológica. 32258 records from Collection Aves (spirit preserved) SMF. 5588 records from Snow Petrel nest census, Mawson region 2004/05. 21 records from RSPB - Twite, winter distribution in Caithness and Sutherland 2006/7. 185 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tinamidae. 6557 records from Perot Museum of Nature and Science. 222 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 45 records from FNL e.V.. 11 records from Kabelskebach (Kabelsketal, Saalkreis). 57 records from Freiburger GEO-Tag der Artenvielfalt. 12 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 25 records from Bayerische Donau - Blindheim Donaubrücke. 12 records from Naturpark Sternberger Seenland. 34 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 14 records from Bayerische Donau - Großmehring. 22554 records from Occurrences des observations de la campagne Suivi Aérien de la Mégafaune Marine en France métropolitaine (SAMM1 - Hiver 2011/2012). 156515 records from Macaulay Library Audio and Video Collection. 595 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 20990 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 4 records from Georgs-Padd (Wangerooge). 1 records from Warnowufer Groß Klein. 103 records from BIRDRACE federleser. 7 records from Langes Tannen(LMS), Klasse 5d. 18 records from BUND Naturschutzzentrum St. Julian. 25 records from "Schwarzwassertal" bei Pobershau. 12 records from Parkuntersuchung Weißer See. 102 records from BIRDRACE HGON Kelkheim-Rumpfteam. 26686 records from Ontario Nest Records. 164150 records from ORN. 10 records from Artenvielfalt auf Restbauernhof. 2872 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 24 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Stercorariidae. 2967 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 27 records from Bad Bodenteicher Heide. 5 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 1310 records from Distribución, abundancia y riqueza específica de la avifauna terrestre en la Isla Espíritu Santo, Baja California Sur, México. 103 records from UC Davis Department of Anthropology Museum. 41420 records from UCLA Donald R. Dickey Bird and Mammal Collection. 12 records from FFH-Gebiet Ahrbachtal. 63 records from Zukünftiges NSG Höftland/Bockholmwik. 48 records from Fuldaaue (Stadtgebiet Fulda). 38 records from Naturgarten Langenholtensen. 131 records from Abundance of birds in the Lena Delta Region. 4 records from Bisons Collection. 247842 records from The Second Atlas of Breeding Birds in Britain and Ireland: 1988-1991. 1 records from Insect Collection (CeStuBio). 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 92 records from Birdrace-Team_BO-bachter-Bochum. 1 records from LauWi. 4 records from Oberservation of birds at station PS14/146 along 49° West. 7 records from Oberservation of birds at station PS14/157 along 49° West. 5 records from Sponges of Rathlin Island. 276 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 813 records from Colección Ornitológica Universidad de Nariño. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 7 records from Heidesee / Halle. 3 records from Oschenberg, NO von Bayreuth-Laineck. 122 records from Birdrace-Hügelland-Mainz/Bingen. 38 records from Streuobstwiese Haus Zeitz. 78 records from BIRDRACE leucorhö statt logorrhö. 53 records from Naturschutzgebiet Lüneburger Heide. 1515 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 88 records from North-west Ireland Machair Breeding Waders 2009.. 25 records from Kashihara City Museum of Insect. 3 records from MAL. 2692595 records from Eremaea. 69 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 31 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 42 records from Schussenaue (Weingarten). 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña marzo 2007. 10 records from Oberservation of birds at station PS14/158 along 49° West. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 5053399 records from Southern African Bird Atlas Project. 13 records from Stever. 2 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 18 records from Kleinstbiotop mit Schulteich/Weißwasser. 11 records from Naturschutzstation Weinberghaus (Dessau). 50 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 355 records from BIRDRACE Havelland. 112 records from BIRDRACE Gütersloher Gimpel. 114 records from BIRDRACE LiLaLau. 6 records from Naturpark Kottenforst-Ville 16.6.09. 78 records from South American Antarctic Marine Biodiversity Literature. 2 records from Araneae Collection. 1 records from Nationalpark Harz Schul-AG Braunlage. 709 records from Upper Silesian Museum, Bird Collection. 8 records from Sukzession Industriebrache. 1 records from AMNH Mammal Collections. 128422 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 113 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 183087 records from MVZ Bird Collection (Arctos). 39 records from Soolbach-Tal. 1 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 16 records from Naturschutzgebiet Börstig bei Hallstadt. 24 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 7 records from Schulhofuntersuchung Thomas-Mann-OS. 2596 records from Collection Ornithologie - ZSRO. 257 records from RSPB - Common scoter national breeding surveys in Britain (SCARABBS). 29 records from Leegmoor (Moormerland/Leer). 8 records from Nottekanal, Klasse 7 - 10. 13 records from Industriegebiet (Kempen). 37 records from Berkel. 12 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 117 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 17 records from Naturschutzgebiet Kochertgraben. 8 records from Schulgelände Erich-Kästner-Schule. 132 records from BIRDRACE Die Wetterauer. 11 records from Tornoer Teich. 2040 records from Perthshire Black Grouse Study Group (PBGSG) - Black Grouse annual lek counts in Perthshire 1990-2009 (Perthshire Black Grouse Study Group). 11 records from Muehlenbach bei Friesheim. 330 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 54 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Jacanidae. 5 records from Collection Paleontology - GPIT. 50 records from MVZ Hildebrand Collection (Arctos). 1 records from Wildnis Erzental. 28 records from TTU Mammals Collection. 31 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 31 records from Lindau im Bodensee. 26 records from Fish Collection of Hokkaido University. 455 records from RSPB - Bearded Tit National Survey in Britain 2002 (SCARABBS). 6 records from Landesgartenschau. 7 records from Langes Tannen in Uetersen. 14228 records from New Mexico Biodiversity Collections Consortium database. 1 records from (Table 1) King penguins' (Aptenodytes patagonicus) path characteristics to their colony, Kerguelen Island. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 26 records from Steinbruch Mainz-Weisenau. 18 records from Wasserwerkspark (Chemnitz). 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 12 records from Erhard Sopp. 8 records from Hoher Stein Kallenhardt. 104 records from BIRDRACE Andechser Stativträger. 42 records from Collection Aves - PUM. 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 1 records from Countryside Council for Wales - Lamprey Survey Data. 50 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 34491 records from Merseyside BioBank - North Merseyside Birds (verified). 631 records from UCM Bird Eggs/Nests Collection (Arctos). 196 records from Australia's Virtual Herbarium. 101 records from Birdrace-Herford-Birder-Herford. 3 records from Fuchsloch (Mohlsdorf/Ostthüringen). 28 records from Wirbach-Taubental (Bad Blankenburg). 312 records from BIRDRACE Gätkes Erben. 157 records from BIRDRACE Rheinische Wasserrallen. 115 records from BIRDRACE Die UHULOGEN. 79 records from BIRDRACE Blinde Hühner. 17 records from Dalbek-Schlucht. 21 records from "Schule am Inselsee" Güstrow. 43 records from Kernberge und Umgebung (Jena). 6 records from Observation of birds at station PS14/151 along 49° West. 58 records from Artenvielfalt am Schlern. 1 records from Reptiles, Amphibians and Fishes collection (ZA) in the Comparative Anatomy Collection of the Muséum national d'Histoire naturelle (MNHN - Paris). 483 records from Nest Specimen. 4 records from CU Invertebrate Paleontology. 205 records from Fortalecimiento de los procesos de recuperación natural y cultural en la Sierra Nevada de Santa Marta. 301 records from Gyeryonsan Natural History Museum Bird . 5 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pipridae. 55 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 1 records from Schulwald Marksuhl. 269 records from BIRDRACE Dithmarscher Deichhühner. 62 records from Schanzenanlage Bergham. 2 records from Bayerische Donau - Riedlingen. 1 records from Tartu University, palaeontology collections. 25333 records from Western Palearctic migratory birds in continental Africa. 26 records from DJH. 10 records from Schaalbach. 30 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 1084007 records from DOF 2001-2006. 4299 records from National System of Protected Areas in Poland - Animals. 97 records from DMNH Eggs. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 13493 records from CRCM Vertebrate Collection. 23 records from Mainufer. 42 records from sbosch. 15 records from Kaniswall/ Gosener Wiesen an der Spree. 270 records from BIRDRACE Niederlausitz-Team. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 2 records from Polish seed gene bank – historical passport data of accessions. 177 records from BIRDRACE Die Kielbris. 1 records from Reifrocknarzissenwiese Löcknitz. 115790 records from LACM Vertebrate Collection. 44 records from Naturhistorisches Museum Mainz, Zoological Collection. 6 records from Harvard University Herbaria. 73 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 53 records from NSG Haunestausee, Hauneteiche. 1258 records from CMC_ornithology_GRC. 6943 records from DMNS Egg Collection (Arctos). 3333 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 110 records from BIRDRACE Angeliter Ornis. 1 records from Geführte Wanderung im Eselsbachtal. 45 records from BIRDRACE Ohne Graureiher läuft nix!. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 14 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 73 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhimidae. 4 records from Naturhistorisches Museum Mainz, Paleontological Collection. 10 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 27 records from Weidenhüttendorf an der Würm (München). 31 records from Seewasen. 21 records from Mißmahlsche Anlage. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 141 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 34 records from Siegen/ Gymnasium Am Löhrtor. 17155 records from MZFC/Coleccion de Aves. 9 records from Naturschutzgebiet Bausenberg (Niederzissen). 13 records from Schulgelände Schule auf der Aue, Münster. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Conopophagidae. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 75 records from Beweidungsprojekt an der Nesse. 161 records from BIRDRACE Nord-Seh-Team. 65 records from BIRDRACE Federal Birds of Investigation FBI. 24 records from Sürther Aue. 2 records from Wahner Heide LK 12 Biologie. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 114 records from Artenvielfalt im Rhein-Neckar-Raum. 10 records from Schulwald Sprendlingen. 5080 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 49 records from GEO Biodiversity Day. 61 records from LaBoOb02. 52 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 79 records from Wupperaue bei Kemna (Wuppertal). 6 records from EDIT - ATBI in Spreewald (Germany). 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 3721 records from Biodiversitätsdatenbank des Landes Salzburg. 24 records from Botanischer Garten (Saarbrücken). 62 records from nazza. 44 records from Wildes Bremer Leben im Park. 70 records from Tag der Artenvielfalt in der Stadt Luzern. 23 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 20 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 2 records from Klimaoasen in Köln. 11 records from Steinbruch Haas Stuttgart-Münster. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 18424 records from Biological and palaeontological collection and observation data MNHNL. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 2446 records from Clare Biological Records Centre dataset. 3 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 11 records from Schulgarten der Volksschule. 3 records from Steinbruch Kronungen. 75 records from BIRDRACE Die Kartoffelsäcke. 1 records from Kleinod unter Hochspannung. 4 records from Schulteich Regionales Förderzentrum "J.H. Pestalozzi" Sondershausen. 1000 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 65 records from Gesamtartenliste Bremerhaven, Helgoland und Sylt. 25560 records from PSM Vertebrates Collection. 81 records from Aves del Santuario de Fauna y Flora Malpelo entre 2006 y 2013. 10 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 32 records from Bodenseeufer Radolfzell. 25 records from Landschaftsschutzgebiet "Holmer Sandberge". 1 records from Tag der Artenvielfalt BUND Kaiserslautern. 18 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 9 records from Flora und Fauna am Mittelrheintal. 1 records from Höltigbaum. 9 records from Neanderthal. 10 records from LSG "Großes Bruch". 82 records from BIRDRACE Buteo2DO. 8 records from Von der Nutzung zur Natur. 152 records from BIRDRACE NAJU-Aspach. 1 records from BB-Biodiversität a. 10710 records from Birds (MNHM-BI). 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 16 records from (Table 1) Diving behaviour of male Adélie penguins (Pygoscelis adeliae) with and without corticosterone implants at Pointe Géologie. 578 records from National Trust - Heigham Holmes species data held by The National Trust. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 25 records from Alien Species in Poland - Animals. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 24 records from Kiesgruben Wemb. 2 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 27 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 13 records from Haarbach Höfe. 256 records from BIRDRACE Upupa epöpse. 177 records from BIRDRACE Mehr Seh Team. 16 records from Projekt Wahner Heide. 296 records from Collection Anatomie Histologie - SMF. 877161 records from Finnish Winter Bird Census. 44 records from Abundance of birds on the channels of Lena Delta in the nesting period. 850 records from RSPB - Crossbills, Distribution survey in Great Britain, 1995-2005 (RSPB). 3818 records from RSPB - Black-throated Diver annual records in North Scotland, 1834-2010, RSPB, SNH, NTS, SWT, RBBP, FCS, Museum Collections . 4105 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 16 records from Wirbach. 29 records from Gelände des Schulzentrums am Himmelsbarg. 14494 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 5046 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 100945 records from UWBM Ornithology Collection. 108289 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 36 records from Südwestlich der Parkwiesen. 5 records from Seed collection – Dead seeds for evaluation and observation purposes. 873 records from Caire-Chabrand Collection. 2277 records from University of Ghent - Zoology Museum - Vertebratacollectie. 604762 records from South Australia Fauna Observations. 35 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 78 records from Birdrace-Die_Laufenten-Braunschweig. 4 records from Ober-Olmer Wald. 10 records from Riekdahler Wiesen. 2 records from Föhrenried. 8 records from Missouri Botanical Garden. 18 records from Schule Sulzbach (Oberegg). 12 records from Pottundkopp. 24 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 46 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 1468 records from Vertebrate specimens of Jyväskylä University Museum. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 39 records from Friedhof Friedenstraße (Berlin). 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hydrobatidae. 4 records from EcoRecord - Mammal records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1985 records from Seabird 2000. 76372 records from DMNH Birds. 35 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 15412 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 39 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 83 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 26 records from Was lebt in der Brutzwiese?. 6 records from Schiller Gymnasium Hof 10b. 23582 records from SBMNH Vertebrate Zoology. 30 records from Gewann Krampf (Heilbronn). 68 records from Riedensee. 4 records from NSG Berschau - Auengebiet (Neustadt / Wied). 11 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 121 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 1 records from Ökosysteme rund um Wedel. 20314 records from Plan de vertebrados de la Patagonia. 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 81 records from Birdrace-Die_Ornithomaten-Herford. 7 records from Naturschutzgebiet Ahrschleife (Altenahr). 368 records from RSPB - Ring ouzel national sample survey in the UK in 1999 (SCARABBS). 735 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 6320 records from inatura - Erlebnis Naturschau Dornbirn. 63 records from GEO-Hauptveranstaltung (Insel Vilm). 9605 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 45 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 1 records from PRECIS. 42480 records from DMNS Bird Collection (Arctos). 120 records from Birdrace-Kosmos_Racer-Freising. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 104 records from BIRDRACE Erlanger Piepmätzchen. 30 records from Umgebung der Gesamtschule Hamburg-Winterhude. 64 records from Kiesbagger (Mittelhausen). 49 records from Faberpark (Nürnberg/Stein). 22 records from (Table 1) Density of seabirds (Fulmarus glacialis, Rissa tridactyla, Larus hyperboreus, Sterna paradisaea, and Stercorarius parasiticus) in Allen Bay 2010. 4 records from Maschwiesen Laatzen. 9 records from Observation of birds at station PS14/156 along 49° West. 3 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 27 records from Umgebung der Grundschule Oderberg. 2995 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 8 records from Lund Museum of Zoology - Insect collections (MZLU). 24 records from Specimens from India at the NTNU University Museum in Trondheim. 8 records from Kindervilla Aussengelände/ Hiltroper Park. 70 records from Birds (SMNH-BI). 111 records from Landesweite NABU-Vogelrallye. 23 records from Prophetensee Quickborn. 661 records from Dumfries & Galloway Nightjar Study Group - Nightjar breeding season surveys in Dumfries and Galloway between 1981 and 2009 (Dumfries and Galloway Nightjar Study Group). 2136 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 52 records from Stadtpark Herzberg (Elster). 5 records from Naturschutzgebiet Ahrmündung (Remagen). 279 records from BIRDRACE Wannacks Topti(c)ker. 24489 records from Institut Mediterrani d'Estudis Avançats: IMEDEA-PALEOVERT. 190257 records from Ontario Breeding Bird Atlas 2001-2005. 5334 records from North Pacific Groundfish Observer (North Pacific Research Board). 15 records from Promberg1. 67 records from "Tre Pini" (Montebelluna, Italien). 61 records from Stadtgebiet (Dannenberg). 46 records from 3. Tag der Artenvielfalt Hockenheim. 9 records from Oberservation of birds at station PS14/145 along 49° West. 631 records from RSPB - 2008 Twite (Carduelis flavirostris) Breeding Season Survey, Wales RSPB/CCW. 4 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 19 records from Butterberg, Dardesheim. 1561 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 865465 records from SEAMAP - marine mammals, birds and turtles. 49352 records from SDNHM Birds Collection. 10 records from Erzental (Oberotterbach). 12 records from Bizzenbachtal (Wehrheim/Taunus). 92 records from Birdrace_TerraCamper-Münster. 50 records from Perchtoldsdorfer Heide. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 101 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 25 records from KUBI Mammalogy Collection. 8460 records from The atlas of breeding birds in Małopolska. 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 3024 records from KUBI Vertebrate Paleontology Collection. 97 records from Birdrace-Die_Nachtraben-Stuttgart. 16 records from Naturschutzgebiet Lochbusch-Königswiesen. 29 records from Kinderbauernhof Pinke-Panke. 42 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 13 records from Olympiapark (München). 105 records from BIRDRACE coesfelder_vogelkundler. 67 records from Wälder bei Nordkirchen. 3 records from Artenvielfalt des "Grünen Klassenzimmers". 57245 records from Bird Observation Data. 1 records from Plant (NHMK-PL). 1 records from Herp Collection. 30 records from Regionalpark(Hattersheim). 37 records from Tag der Artenvielfalt. 1291 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 1180 records from Birds fallen at Danish Lighthouses 1883 through 1939. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 9 records from Steinbruch Mainz-Weisenau, 3. Jahr. 112 records from BIRDRACE Hügelland zu Fuß. 98 records from GEO-Hauptveranstaltung in "Wildtierland". 2 records from Rur. 3 records from Raus in die Natur. 65 records from Programa de erradicación de los roedores introducidos en la Isla Rasa, Baja California: un plan de restructuración ecológica. 755472 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 134077 records from Israel Nature and Parks Authority. 634258 records from Hawk Migration Association of North America - HawkCount. 19 records from VSN-Wiese. 1662 records from DINA. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 7000 records from CCBER Ornithology Collection. 97550 records from CAS Ornithology (ORN). 5240 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 150 records from Birdrace-Ostseevögel-Ostvorpommern. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 22 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 110 records from BIRDRACE Linumer Luchschleicher. 692 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 41 records from LBV 100 - Artenvielfalt am Rothsee. 38 records from SOMBASE. 1405 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AVES. 22366 records from Bird Collection. 32 records from Stadtpark Sulzbach-Rosenberg. 2 records from Schulgarten Paul-Schneider-Schule, Münster. 62 records from Walldorf-Wiesloch: "Natur über den Gleisen". 357 records from Collembola Collection. 1784898 records from SAFRING. 10 records from Naturpark Kottenforst-Ville 19.6.09. 121 records from Birdrace_Deutschlands_enthusiast.Vogelkucker-Münster. 119 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 2475 records from HSU Wildlife Eggs and Nests. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 144 records from BIRDRACE Die Mohrenlerchen. 106 records from BIRDRACE Ave Goettingen!. 4 records from Seeufer ehem. BUGA-Gelände. 6654 records from Observaciones de Especies Silvestres (by Charif Tala). 1 records from Alien Species in Poland - Plants. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 3 records from Fledermaus. 1454 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 61 records from BIRDRACE Kollektiv Eisente. 6383 records from RSPB - RSPB Reserves breeding bird surveys. 31046 records from MSB Bird Collection (Arctos). 4251 records from Aves de la cuenca media del río Chambery, Caldas. 1621 records from Ornithologie ZMK. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cinclidae. 10 records from Schulgarten Hans-Carossa-Oberschule. 11 records from Schafheide im Böblinger Wald. 1 records from Waldtag in und um Seelingstädt. 102 records from BIRDRACE Niederrheinische Bartgeier. 44 records from Schloss Fasanerie Eichenzell. 1178 records from Birds (NMNO-BI). 19 records from Gelände des IVL (Zeckern). 1 records from Artenvielfalt im Umfeld der Burgwegschule. 138 records from Birdrace_MarschPIeper_Pinneberg. 710 records from National Invasive Species Database. 4 records from Nachtaktiv im Ökogarten (Bad Waldsee). 4 records from Wiesen am Treffpunkt Freizeit. 888 records from Insecta ZMK. 764 records from IndOBIS, Indian Ocean Node of OBIS. 20 records from Ökostation (Freiburg). 21 records from Artenvielfalt der Nordsee - Sylt. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 28941560 records from Artdata. 118 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 3 records from Nationalpark Jasmund. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 30 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 44 records from Entdeckertour am Muldestausee. 9 records from Unterbrucker Weiher. 134 records from Birdrace-Raumpatrouille_Oriolus-Münster. 5852 records from Queen Victoria Museum Art Gallery provider for OZCAM. 330 records from RSPB - Red-Throated Diver National Survey in Britain in 2006 - 5km square summary (SCARABBS). 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust, . 22 records from Wiesenbiotop am Wasserturm. 55 records from WildesMoor bei Schwabstedt. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Chionidae. 4 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 200 records from Queensland Museum provider for OZCAM. 166 records from RSPB - Redshank nesting on saltmarshes in Britain (RSPB). 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 19311 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 2413 records from Literature based species occurrence data of birds of North-East India. 12 records from LK 11 im Mönchspark. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1 records from Collection Crustacea - ZMB. 351 records from Bird tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 11800 records from UCM Bird Collection (Arctos). 39 records from Langes Tannen (Uetersen). 160 records from Eppingen und Umgebung. 33 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 128 records from BIRDRACE Oostfreesland Bird-Lopers. 43443 records from Royal Museum of Central Africa - Albertian Rift Birds (ENBI wp13). 103 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thamnophilidae. 87134 records from Sheffield Bird Study Group - Sheffield Bird Study Group (Yorkshire records). 1562 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 51 records from Artenvielfalt Kreis Gießen. 79 records from Birdrace-Bielefinken-Bielefeld. 122 records from Sudeniederung (Amt Neuhaus). 76 records from Schulzentrum "Parc Hosingen". 95 records from BIRDRACE accipiter hardcore birding. 40 records from Kühmark bei Wetzlar. 2037 records from Birds (ENHM-BI). 2137 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 34899 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 15883 records from Canadian Lakes Loon Survey. 21 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 71 records from Gemeinde Sursee. 26 records from Danisco-Wiese. 16 records from Schulprojekt (Bremen). 123 records from Birdrace-Professorenteam-Münster. 69 records from Abundance of birds on the channels of Lena Delta in the brood period. 92 records from Abundance of birds on the channels of Lena Delta in the fall migration period. 8 records from Oberservation of birds at station PS14/143 along 49° West. 29 records from Klostergarten St Luzen. 5 records from Botany (UPS). 15944 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 10995 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups. . 2 records from Artensuche auf den Elbwiesen in Radebeul. 16 records from Park Schönfeld (Kassel). 13 records from Waldi-Weiher. 5 records from Tongrube bei Hettstedt. 5 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 8 records from Artenvielfalt und Kulturlandschaft. 127 records from BIRDRACE Southernmost Lakers. 13 records from FFH-Gebiet Klosterwasser/Burkau. 24 records from Waldstück Bremerhagen LK Bio Kl. 12. 2 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 126 records from BIRDRACE Duckehühnchen. 51 records from Biosphärenpark Wienerwald - Pfaffstätten. 5 records from Lebensraum Walram. 2 records from MSB Parasite Collection (Arctos). 30 records from Priest Pot species list, Cumbria, Britain. 84 records from Schloß Türnich (Kerpen). 42 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 1121 records from Ice and animal observations during POLARSTERN cruise ANT-X/6. 37 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 830167 records from AMNH Bird Collection. 113482 records from KUBI Ornithology Collection. 26 records from Bioimages. 12682 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 16344 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 11 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 144 records from BIRDRACE Birding Bentheim. 143 records from BIRDRACE Die Laufenten. 1 records from Naturpark Kottenforst-Ville 17.6.09. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 8072 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 43 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 12 records from Naturgrundstück (Eutin). 4 records from "Schwarzes Teich" (Waldpark Radebeul). 134 records from Birdrace-Team_Havelland-Havelland. 1 records from Wattuntersuchung (Cuxhaven). 5 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 278 records from BIRDRACE Usedommeln. 118 records from BIRDRACE Die Lippegeier. 14 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Sungei Buloh - Mangrovenwald. 60000 records from Birds (NSMK-BI). 3 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 69 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 469 records from Makira. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 45948 records from Museum Victoria provider for OZCAM. 498478 records from NMNH occurrence DwC-A. 110 records from Birdrace-LiLaMai-Vechta. 1 records from Landschaftsschutzgebiet Buchhorst 3. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 27 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 5 records from Rechts des Inn Höhe Hofau Rosenheim. 1 records from Grünanlagen Stadt Brandenburg an der Havel. 8 records from Exkursion Ebertsheimer/Grünstädter Berg. 39 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Phoenicopteridae. 5 records from Plant (NSMK-PL). 21000 records from Akita Prefectural Museum:Observation Records of Birds in Akita Prefecture. 163560 records from Bird specimens. 78 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 24 records from Wald und Wiese am Buchwald. 7 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 11 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Diomedeidae. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 3 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 7 records from NRM-Herpetology. 59 records from Biotope in Rheine - Aktion 350. 1 records from Molche in Ruschwedel. 1 records from Ober-Olmer Wald 09. 645 records from Marine birds and mammals of the Southern Ocean (a census for the CAML). 3631 records from Collection Ornithologie - SNSD. 54 records from Artenvielfalt der Nordsee - Bremerhaven (Dorum-Neufeld). 16 records from Biotop Binsenwiesen (Wehrheim/Taunus). 17 records from Altenburg bei Bamberg. 4 records from Klosterwald Itzehoe. 55349 records from Australian Museum provider for OZCAM. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 1394 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 79 records from RSPB - Black grouse lek survey in Sutherland 2008-9 (RSPB). 11 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 22099 records from Colección nacional de zoología. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 33484 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 356 records from Morphologische Daten von Puffinus creatopus. 542 records from NCSM Vertebrate Paleontology Collection. 38 records from Gieselbachtal Fulda-Harmerz. 22 records from Leben im Finkensteiner Moor. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 1 records from Riedkanal Bötzingen. 5 records from Schulhof A.-Lindgren-Schule (Elmshorn). 17 records from Tierpark Zittau. 254 records from BIRDRACE Thüringer Becken-Birders. 160 records from Duck sightings per month, Macquarie Island. 44 records from Klutensee. 18 records from Langes Tannen. 94 records from Birdrace-Filz_Fledermäuse-Münster. 47 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 2222 records from UWYMV Bird Collection (Arctos). 7320 records from Aves Collection of Institute of Systematics and Evolution of Animals. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 2 records from Specimens from India at the University Museum at the University of Bergen. 2 records from CAS Ichthyology (ICH). 2 records from VFD-H: Rheingau: Pferdeweide Loock. 11 records from Südpark (Bochum-Wattenscheid). 14 records from Artenvielfalt im Beckerbruch (Dessau). 1 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 32 records from Biosphäre Bliesgau. 1 records from Mittelriede Höhe Gliesmarode-Braunschweig. 337 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Falconidae. 1 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 6758 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 31 records from Klasse 3a. 6 records from Rund um das LUGY. 1 records from Glemstal (Leonberg). 44 records from Weinberg Reichersdorf. 1 records from Naturpark Kottenforst-Ville 18.6.09. 3 records from Naturnachmittag 'Artenvielfalt an der Ecke' (Wäldchen an der Wegegabelung). 26 records from Landschaftspflegehof (Berlin). 4 records from Collection Cnidaria SMF. 10885 records from RSPB - Swift Inventory of Nest Sites in the UK, 2009 (RSPB and Swift Conservation Groups). 56 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 72 records from Bioblitz 2013 Copenhagen Denmark. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 153532017 records from EOD - eBird Observation Dataset. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 126 records from Birdrace_Schräge_Vögel-Herford. 62 records from Kremmer Luch. 11 records from Roter Berg Werdau (Leubnitz). 18 records from Spießwoogtal / Königsbruch (Fischbach). 14 records from Schulgelände Kranich-Gymnasium (Salzgitter). 21 records from Müritz-Nationalpark. 84 records from BIRDRACE Bielefinken. 103 records from BIRDRACE Die Otzberger. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 128 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2007. 8 records from 2. Aspacher GEO-Tag der Artenvielfalt. 8 records from Trockenhang Greinhartsberg Edelfingen. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 494932 records from Field Museum of Natural History (Zoology) Bird Collection. 114 records from Birdrace-Finkenspötter-München. 2 records from Schulhof Liebfrauenschule Oldenburg. 139 records from BIRDRACE Guckers Offenbach. 114 records from BIRDRACE Di-Bi-Di-Birder. 31 records from Eschlberg Thalhausen. 9 records from Weinberge und angrenzende Felsflächen (Drieschen) in Hatzenport/Terrassenmosel. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Donacobiidae. 107 records from RSPB - Crested tit wintering survey in the UK, 1992-1995 (RSPB). 296 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rallidae. 6312 records from University of California Museum of Paleontology. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 27 records from Stadtpark Prinzengarten (Sigmaringen). 69 records from BIRDRACE Pfeifenten. 116 records from BIRDRACE Die TUErteltauben. 2 records from NABU-Fläche am Bösselhausener Weg. 177 records from Bay of Fundy Species List (OBIS Canada). 18 records from Stadt Königs Wusterhausen. 2 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pelecanoididae. 20 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 18 records from Truppenübungsplatz Panzerkaserne Böblingen. 5 records from NSG Forst Zinna-Jüterbog-Keilberg. 66 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 106 records from Sylter Meerstrandläufer. 1687 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2007. 1480 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 63 records from NSG Karwendel. 46834 records from Birds (KIDR-BI). 1 records from Seil Natural History Group - SNHG Biological Records Dataset. 6 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 38 records from Küstenschutzwald. 10 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 16 records from Steinbachtal (Würzburg). 3 records from VFD-HH/SH: Pferdweide Lammert. 505 records from Avifauna de la Isla de Cozumel, Quintana Roo_2. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 96 records from Birdrace-federleser-Herford. 4 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 49 records from Wulfsmuehle/Pinnau. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 17 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 32 records from Pöhlberg bei Annaberg. 109 records from BIRDRACE Die Borner. 69 records from BIRDRACE Mathilden-Käuze. 2883 records from Inventory of Antarctic seabird breeding sites. 166 records from Arizona State University Bird Collection. 3 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 15 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 40 records from Heinersdorfer Sumpfwiese. 5 records from Hemmerder Schelk (Unna). 1 records from Spandau HBO. 2 records from Collection Paläobotanik SMB. 1 records from KTU Pteridophyta. 1 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 5 records from Hainbachtal in Oelsnitz/V.. 119 records from BIRDRACE Immerwiederhopf. 1 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 2 records from Marine Biological Association - Marine Life Survey Data (collected by volunteers) collated by MarLIN. 2 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 874 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 2291 records from Bird Collection. 13 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 69 records from Bergkamen- Bergehalde Großes Holz. 16 records from Waldwandel in Monschau-Mützenich-Boverei. 51 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 241 records from BIRDRACE RennVögel Münsterland. 75 records from Spechtwald. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 107 records from BIRDRACE Diesmal sehen wir mehr. 1429 records from Tullie House Museum - Tullie House Museum Natural History Collections. . 76 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 3 records from Aktionstag Wiese am Vogelhammerkopf. 12031 records from UNSM Vertebrate Specimens. 4978 records from Staffordshire Ecological Record - SER Site-based Surveys. 44 records from 20 Jahre Naturschutzgebiet Dreienberg. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 9544 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 4347 records from Aves Acuáticas en el Caribe Colombiano Entre 2007 y 2009. 2 records from Wasserbachsee. 3385 records from Avifauna de la laguna Madre de Tamaulipas. 9728 records from Birds of Ireland. 123 records from Birdrace-SportfreundeTriller-Münster. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 2571 records from RSPB - Black grouse surveys in Dumfries and Galloway 1980-2005 (RSPB and the Southern Uplands Partnership). 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 72 records from Birdrace-Buteo2DO-Dortmund. 88 records from Birdrace-WeserEggeLäufer-Höxter. 9 records from Feriendorf Ober-Seemen. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 15 records from Heider Bergsee (Brühl). 95 records from BIRDRACE BiBi. 9 records from Lustbach-Umland. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 11250 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 6 records from GEO-Tag am Hohlen Stein. 1576 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 85 records from RSPB - Black grouse lek survey in Ross-shire. 248496 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) . 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 21 records from Am Moosangerweg. 9 records from Stadtbiotop Ulrichteich. 4 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 3 records from Schulumgebung Grüterschule, Rheine. 11 records from Lüner Holz (Lüneburg). 7 records from Colección de moldes endocraneanos del CENPAT. 118 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 2967 records from Paleobiology Database. 177 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Emberizidae. 263017 records from European Seabirds at Sea (ESAS) bird sightings from 1980 to 2003.. 5 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 341899 records from Museum of Comparative Zoology, Harvard University. 1594 records from Musée Vert ornithology collection. 22 records from Förderzentrum Schmölln. 21 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 15 records from Wassermann. 91 records from BIRDRACE SchrägeVögel. 2 records from Herpetology Collection. 21 records from Die Teiche im Britzer Garten. 44 records from Pfingstexkursion Alter Bessin. 19 records from Überall ist Wunderland. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 1998 records from Aves de la cuenca media del río Bogotá. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 27 records from Vögel. 269 records from BIRDRACE Kosmos-Racer. 2 records from Wälder im Hainbachtal. 228981 records from NatureServe Network Species Occurrence Data. 926 records from Zoological collections of the University of Tartu. 4723 records from Bird collection of National Museum of Nature and Science. 71 records from Neckartalsüdhang (Horb). 18743 records from Staffordshire Ecological Record - SER Species-based Surveys. 465 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 620 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 26 records from Draubiotop Lavamünd. 52 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Casilda (Luna & Piazza, octubre 1999). 274 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 535 records from Kieppi bird collection. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 11013 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 18 records from Ehmkendorf. 128 records from Birdrace_turbine_untersee-Konstanz. 10 records from Wattenmeer-Safari (Wurster Watt). 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 287 records from BIRDRACE Pody und Co. 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 2940 records from RSPB - Cirl bunting national surveys in the UK (SCARABBS). 40 records from Wanderweg am Windebyer Noor (bei Eckernförde). 9 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 5 records from Observation of birds at station PS14/152 along 49° West. 196 records from Inventario de Aves en la Finca Naranjitos; Aracal, Yopal, Casanare. 30878 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 30 records from Countryside Council for Wales - Freshwater Site Visits. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 1 records from Paleontological collection of the National Museum - Flora. 60571 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 2 records from Countryside Council for Wales - Shad Monitoring data. 4 records from Regenrückhaltebecken Bad Bevensen. 32 records from Bannwald Burghauser Forst. 131 records from BIRDRACE Brut. 2 records from Liether Park 1 (LMS), Klasse 5b. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 20 records from Vogelwelt im Europa-Rosarium. 29 records from Innenstadt Göttingen - Natur Zuhause. 559 records from Greater Manchester Ecology Unit - Distribution of Species of Conservation Interest in Greater Manchester. 156 records from Royal penguin Eudyptes schlegeli census and observations at North Head, Macquarie Island 1952/53. 14 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 338394 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 2392 records from CHAS Vertebrates. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 76 records from Birdrace-Birding_for_Nature-Bonn. 6 records from Alter Nördlicher Friedhof (München). 16 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 11 records from NABUGEO1. 19 records from Industriebrache (Kempen). 12 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from Landwehrbach. 48566 records from North West Territories and Nunavut Bird Checklist, Canada. 1075 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo Páramos Chilí - Barragán, Tolima. 570 records from Museum of Zoology, University of Navarra. 321 records from STAMP seabird egg collection. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 4 records from Sandhofen. 13 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 63 records from Biologische Station im Kreis Wesel. 62371 records from MLZ Bird Collection (Arctos). 1218 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Odontophoridae. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Heliornithidae. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 8 records from Oberservation of birds at station PS14/149 along 49° West. 37 records from Ostfriesland. 273 records from National Trust - Ickworth species data held by The National Trust.. 1324115 records from Garden Bird Surveys. 95 records from Birdrace-Buteo1_DO-Dortmund. 146 records from BIRDRACE VdW Wilder Westen. 21 records from Von Elf bis Elf" Der Botanische Garten Wuppertal. 2474 records from Baillon Collection. 22700 records from Royal British Columbia Museum. 3 records from MfN Fish Collection, Zoology. 20 records from Schulhof und Anlagensee in Nellingen. 1400 records from Bird specimen detabase of Kanagawa Prefectural Museum of Natural History. 9 records from MSB Mammal Collection (Arctos). 18970 records from Cowan Tetrapod Collection - Birds. 3 records from NRM-Fishes. 5 records from Albany Museum Grant. 120 records from BIRDRACE Ornis im Einsatz. 7 records from CNMA/Colección Nacional de mamíferos. 57 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tityridae. 85 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 66 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 39 records from Triebesbach (Zeulenroda-Triebes). 17 records from Streuobstwiese Stedar 2009. 3 records from Northern Territory Museum and Art Gallery provider for OZCAM. 23417 records from Korea Bird Distribution Atlas Database. 25 records from Naturnahes Tal in Siena. 413272 records from DATAVES. 381 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 17 records from The Bat Conservation Trust - The BCT/MTUK Bats & Roadside Mammals Survey. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 285 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 2 records from Kochertgraben II. 8 records from Stausee Weiditz. 76 records from BIRDRACE Nachtigallen. 84 records from BIRDRACE Vogelscheuchen. 14 records from Rosarium (LMS), Klasse 6a. 3 records from Fossil (WSHN-FO). 5 records from Penguins of Antarctica. 2 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 4417 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 543 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 1 records from Bohart Museum of Entomology, UCD. 52 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 50 records from Gemeindegebiet Weikendorf (Marchfeld). 13 records from Oberservation of birds at station PS14/159 along 49° West. 2 records from Type Localities for organisms and fossils first described from Antarctica. 708 records from RSPB - Black Grouse Trial Management Project Data, South-West and North Scotland, 2007-2012 (SNH, RSPB, FCS). 781 records from RSPB - Bittern Annual Surveys in Britain 1990-2008 (SCARABBS). 74 records from Carabidae of Poland. 9052 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 11 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 105 records from BIRDRACE Kiesmätze. 13 records from Lebensraum Dorf. 12 records from Werl macht sich auf die Suche. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 8527 records from HSU Wildlife Birds. 16732 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 210 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Mimidae. 342 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 6 records from Waldsee. 21 records from Ortelsbruch - Hangmoor bei Morbach. 29 records from Selztal bei Friesenheim. 24 records from Ornithologische Wanderung um Tussenhausen. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 19 records from Gronau - auf der Suche nach dem Neunauge. 6 records from Schulgarten Janusz-Korczak-Realschule. 1770 records from Schmidt Museum of Natural History_Birds. 1 records from Rund um die Sausenburg. 2 records from Steinbruch Mainz-Weisenau, 4.Jahr. 2 records from NSW herbarium collection. 4 records from Artenbestimmung. 8 records from Freiheitsring (Frechen). 3 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 123562 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups. . 6394 records from Censos de aves del parque nacional Laguna Blanca. 545 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 59849 records from QLD DERM Coastal Bird Atlas (Trial). 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 7530016 records from Birds Australia, Birdata. 6 records from Sahrbachtal Kreis Ahrweiler. 15382 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 62456 records from RBINS collections. 88335 records from Canadian Museum of Nature Bird Collection. 31 records from Frauenholz (Holzmaden). 43443 records from rmca-albertine-rift-birds. 55103 records from CUMV Bird Collection (Arctos). 871101 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 39011 records from Merseyside BioBank - North Merseyside Birds (unverified). 60 records from Wangerooge. 13 records from Binsenwiesen. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 166 records from BIRDRACE Die Düsselmöwen. 137 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 35 records from Naturpark Drömling. 3687 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 16 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 32 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 176 records from BIRDRACE Professorenteam. 155 records from Birdrace-Gätkes_Erben-Lüneburg. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 62 records from Marine Conservation Society - Seasearch Marine Surveys . 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1 records from Incorporación de nuevos registros de mamíferos de la región Sierra Norte de Oaxaca. 1854 records from IIAPPoa. 1 records from Herpetology. 18 records from Biotope auf dem Gelände der Eggerstedt- Kaserne in der Nachbarschaft der Theodor-Heuss-Schule. 4 records from Wiese am Waldrand (Gurtweil). 3060 records from MSB Host Collection (Arctos). 178 records from RSPB - Corn bunting surveys on the Western Isles. 140634 records from Estonian Nature Observations Database. 1105 records from Birds of Cisna Community (southern Poland). 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 1658 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 33 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 5 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 85 records from Birdrace-Die_Paradiesvögel-Herford. 4 records from Örtzemündung (Stedden). 71 records from Birdrace-do_elster_Dortmund. 2 records from Tiere. 99 records from BIRDRACE TEAM BO-BACHTER. 101 records from BIRDRACE nabu-rhein-main.de. 8 records from Leben auf einer Sturmfläche. 130 records from BIRDRACE - The famous Grouse feat. The James. 408 records from Akita Prefectural Museum＋Birds Specimens of Akita Prefectural Museum. 1251 records from Atlantic Canada Conservation Data Centre (OBIS Canada). 35 records from (UTCFB) University of Tennessee - Fossil Birds Collection. 63 records from GEO-Hauptveranstaltung (Duisburg). 27 records from schulgarten. 5056 records from Nest census, Windmill Islands 2002/03. 17202 records from Wetland Inventory (NV). 46 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 6015 records from UTEP Vertebrates. 24 records from Hare Survey of Ireland 06/07. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 205617 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 69 records from Birdrace-NAJU_Aspach-Rems/Murr. 2 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 4 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 104 records from BIRDRACE Die Göttinger Sozialbrachvögel. 3339283 records from naturgucker. 34 records from Donauinsel des BN bei Entau. 557 records from RSPB - Corn bunting breeding distribution in Scotland (RSPB/Volunteers). 2 records from Fluss - Vielfalt. 38 records from Fossil (MNHM-FO). 151997 records from Seabirds of the Southern and South Indian Ocean. 1 records from Gwaii Haanas Invertebrates (OBIS Canada). 1 records from MSUM Ichthyology and Herpetology Collections. 79 records from GEO Hauptveranstaltung Tirol (Innsbruck). 22 records from Artenvielfalt der Nordsee - Helgoland. 4 records from Wiese und Weide am Waldrand von Gusterath. 23 records from Streuobstwiese Kattenhund (Schleswig). 42 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 38 records from RSPB - Lesser Spotted Woodpecker sample survey in England 2007. 2 records from DORSA - German Orthoptera Collections. 10273 records from BIOLOGICAL SCIENCES DATA. 10909 records from Irish Wetland Birds Survey (I-WeBS) 1994-2001.. 26173 records from Bernice P. Bishop Museum. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 218255 records from Norwegian Biodiversity Information Centre - Other datasets. 15 records from Brander Wald (Stolberg). 16 records from Grillhütte Wettsaasen, Wiese, Hecken. 2 records from VFD-H: Heidenrod: Pferdeweide Mürth. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 9 records from Schulgarten-St.-Georg-Gymnasium. 1 records from Eichendorf Weiher Schwalbach a.Ts.. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 102 records from BIRDRACE Buteo1DO. 107 records from BIRDRACE Herford Birders. 55 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 1019 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 928561 records from Point Reyes Bird Observatory - Point Counts. 61130 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 13 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 14 records from Im Bauerngarten. 24 records from Kloster Eberbach. 1 records from Paul-Gerhardt-Schule Dassel. 96 records from BIRDRACE OAG Neuwerk. 119 records from BIRDRACE Tick, Trick und Track. 83 records from BIRDRACE Die Frankenpfeifer. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 28 records from Ortsrand Zandershagen. 234882 records from ARGOS Satellite Tracking of animals. 425 records from ANTXXIII-8 Birds and Mammals. 15 records from Natur aus zweiter Hand am Muldestausee. 64 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 7 records from Küste Wismar-Wendorf bis Hoben. 79 records from Kühnauer See (Dessau). 47 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 5363 records from Colección Ornitológica de la Universidad del Valle. 691 records from RSPB - Black grouse national surveys (SCARABBS). 1198 records from Wildlife Sightings. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 77084 records from Australian National Wildlife Collection provider for OZCAM. 21083 records from NCSM Birds Collection. 31 records from Grenzturm Hohen Neuendorf. 4 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 13 records from GE-Brühl. 5 records from Kaisertal. 17 records from Wiese hinter der Schule (Darmstadt). 1 records from Kaltenkirchen Brache. 96 records from BIRDRACE Emslandracer. 98 records from BIRDRACE Die Paradiesvögel. 13 records from Owere Fiddel. 2 records from Feuchtwiese Grüne Mitte, Klasse 5a. 109 records from ZFMK AMIBIO. 204 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 95 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 39 records from Gurgltal (Tarrenz). 46 records from Quarrendorfer Landschaftsschutzgebiet. 2 records from Die Wuhle. 1 records from Weidewirtschaft. 4472 records from MVZ Bird Observations (Arctos). 5 records from Expedition "Schulgelände". 97 records from BIRDRACE NABUhu Trier!. 82 records from Tag der Artenvielfalt in Heidelberg. 13 records from "Ahrschleife bei Altenahr". 4 records from Stadtwald Heide. 601516 records from Watervogels - Wintering waterbirds in Flanders, Belgium. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 2952902 records from DOF. 18471 records from Collection Aves (bird skeletons) SMF. 40316 records from The Scottish Ornithologists' Club - Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - non-sensitive species. 1 records from Lund Botanical Museum (LD). 54 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Ciudad Pérez (Luna & Luna, octubre 1999). 650 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anatidae. 201121 records from Geographically tagged INSDC sequences. 86 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 439 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 72 records from Baggerseen bei Krauchenwies. 802 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 1 records from MfN - Auchenorrhyncha Collection. 119 records from (UTCB) University of Tennessee - Birds Collection. 53 records from Königstetten. 47 records from Freiburger Tag der Artenvielfalt. 5 records from Luch Niederlehme, Schüler der Klasse 7. 31 records from Bergbaufolgelandschaft am Muldestausee. 29 records from Werremündung im Schwarzatal. 135656 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 17 records from Royal Botanic Garden Edinburgh Herbarium (E). 50504 records from Ditsong Museum. 24 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Phalacrocoracidae. 2407 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 26880 records from KUBI Ornithology Tissue Collection. 1 records from Biotop "Kohlbeke" (Berlin-Marzahn). 2 records from Wedeler Au. 43 records from Ried und Sand - Artenvielfalt durch Beweidung. 8 records from Flora und Fauna am Mühlberg. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 7 records from Mangfalltal. 25 records from Naturschutzgebiet Müchelholz (Mücheln). 10 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 4 records from Dreilinden Gymnasium-Schulgelände. 124 records from Birdrace-LohmannsAdleraugen-Münster. 116 records from UAM Earth Sciences Collection (Arctos). 16 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 2 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 9 records from Tanzanian Vertebrate Collection. 5 records from Schulgelände IGS Kaufungen. 128 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 36 records from Umgebung der Gesamtschule Winterhude (Hamburg). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae.
Keywords: GBIF; biodiversity; species occurrences